1997
DOI: 10.1046/j.1365-2133.1997.d01-1232.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthralin (dithranol)in vitroinhibits human monocytes to secrete IL-6, IL-8 and TNF-α, but not IL-1

Abstract: Anthralin is a most widely used compound for topical treatment of psoriasis. Whereas numerous studies have ascertained anthralin as a safe and effective drug its mode of action still remains unclear. Previous studies demonstrated dose-dependent inhibition of a number of pro-inflammatory functions in human neutrophils and monocytes (MO). The aim of the present study was to investigate in stimulated MO the effect of anthralin on the secretion of cytokines which are of known importance for the psoriatic tissue re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Early, extracellular control of GM-CSF and TNF-␣ induction may provide a temporal advantage in amplifying the bioactivities of subsequently expressed chemokines and infiltrating leukocytes. Anthralin has also been reported to reduce the secretion of LPS-induced cytokine release by monocytes, including IL-6, IL-8, and TNF-␣ [33], although the significance of this observation is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Early, extracellular control of GM-CSF and TNF-␣ induction may provide a temporal advantage in amplifying the bioactivities of subsequently expressed chemokines and infiltrating leukocytes. Anthralin has also been reported to reduce the secretion of LPS-induced cytokine release by monocytes, including IL-6, IL-8, and TNF-␣ [33], although the significance of this observation is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Also, anthralin suppresses transcription of transforming growth factor-· mRNA in keratinocytes, as well as decreases epidermal growth factor receptor binding by reducing affinity of this receptor for its ligand [26]. Moreover, an immunosuppressive effect of anthralin has recently been proposed, such as inhibition of the secretion of interleukin-6 (IL-6), IL-8, and tumor necrosis factor-· from lipopolysaccharide-stimulated human monocytes [12]. Anthralin has recently been shown to exert a potent effect on keratinocytes and mononuclear cells through strong induction of lipid peroxidation and JNK activation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Anthralin inhibits keratinocyte hyperproliferation and granulocyte function [7,11,12]. Although the mode of action of anthralin is not completely clear, it is reported that anthralin is susceptible to rapid photo-or autooxidation, generating secondary reactive oxygen species, which are supposed to inhibit cell proliferation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a large number of clinical and experimental data the mode of therapeutic action of anthralin in psoriasis is still poorly understood. Various investigators have shown that anthralin inhibits key enzymes of metabolic pathways, cellular respiration and DNA synthesis [3] and exerts distinct immunomodulatory effects [4,5].…”
Section: Introductionmentioning
confidence: 99%